Rambo [videorecording (DVD)] : first blood part II - Cosmatos, George P.; Stallone, Sylvester; Stallone, Sylvester; Crenna, Richard, 1927-2003; Napier, Charles, 1936-2011 (Lions Gate Home Entertainment, 2006)
John Rambo returns to Vietnam to find and rescue a group of American P.O.W's that have been there since the Vietnam War.